ACCOUNTING AND REPORTING STANDARDS FOR CORPORATE FINANCIAL STATEMENTS 1957 REVISION. (The Accounting Review, 1957)
The article presents the accounting and reporting standards for corporate financial statements. The primary function of accounting is to accumulate and communicate information essential to an understanding of the activities of an enterprise, whether large or small, corporate or non-corporate, profit or non-profit, public or private. Accounting procedures and reports are based on the premise that quantitative data provide an effective means of description and are basic to the communication of qualitative information about the enterprise. Financial statements are based on conventions derived from experience. These conventions represent the accountant's best efforts to meet recognized needs in the most useful manner. Underlying the conventions of accounting are a number of concepts: business entity, enterprise continuity, money measurement and realization. Assets are economic resources devoted to business purposes within a specific accounting entity; they are aggregates of service-potentials available for or beneficial to expected operations. The significance of some assets may be uniquely related to the objectives of the business entity and will depend upon enterprise continuity. Uniformity of accounting method is neither expected nor necessarily desirable, but reasonable comparability of reported data is essential.